Poems of Zahid Dar - Muhammad Rashid (بازیافت, 2023)
<span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-bidi-language: ER;">Nazm is a major part of Urdu that is normally written in rhymed verse and also in modern prose-style poem. Nazam is a significantly written by controlling one's thought and feelings. Which are constructively discussed as well as developed and finally, concluded, according to the poetic laws. In this research paper, I have differed with Zahid Dar's traditional way of poetry and I have made the topic of his achievements in modern poetry. <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-bidi-language: ER;">There are three types of Nazam Daoband Nazm, Azad Nazm and Nasri Nazm. <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-bidi-language: ER;">Some famous poets of Azad Nazm. Noon Meem Rashid, Faiz Ahmad Faiz, M. Hussain Azad, Anees Nagi and Iftikhar Talab.